Understanding the Intergenerational Transmission of Human Capital: Evidence from a Quasi‐natural Experiment in China. Issue 2 (24th May 2016) - Zhou, Dong; Dasgupta, Aparajita
Abstract: This paper exploits the closure of senior secondary schools in urban China from 1966 to 1971 in order to identify the causal intergenerational transmission effects of education. The paper uses the instrumental variable approach to examine the intergenerational causality of educational transmission at the senior secondary schooling level in urban China. The exogenous variation in parental senior secondary educational attainment both over time and across regions allows us account for selection bias and thus identify the causal intergenerational transmission effect in education. We further show that our conclusion is robust to alternative identification strategies and data sets.